The Influence of Cognitive Behavior Therapy (CBT) Approach Group Counseling in Reducing Hedonistic Behavior in Students of SMK N 1 Koto Baru Dharmasraya - Lestari, Diyah Ayu; Silvianetri, Silvianetri (Yayasan Minang Darussalam, 2025)
Background. Hedonistic behavior among students is increasingly prevalent and poses a serious threat to academic discipline, financial responsibility, and moral development. This lifestyle, often characterized by excessive consumption, materialism, and instant gratification, can hinder students' focus and future orientation. Cognitive Behavior Therapy (CBT) is a structured and goal-oriented therapeutic approach that has shown effectiveness in modifying irrational beliefs and maladaptive behaviors. Purpose. This study aimed to determine the influence of group counseling using the CBT approach in reducing hedonistic behavior among students of SMK N 1 Koto Baru Dharmasraya. The research also sought to identify the specific aspects of hedonistic tendencies most affected by the intervention. Method. This study used a quasi-experimental design with a pretest-posttest control group. The sample consisted of 20 students identified with high levels of hedonistic behavior, divided equally into experimental and control groups. The intervention consisted of six CBT-based group counseling sessions over three weeks. A validated hedonism behavior scale was administered before and after the sessions. Data were analyzed using paired t-tests and independent t-tests. Results. The results showed a significant decrease in hedonistic behavior scores in the experimental group after the counseling sessions, while the control group showed no significant change. Aspects such as impulsive spending, dependence on peer approval, and time mismanagement were notably reduced among the participants who received the intervention. Conclusion. Group counseling using the Cognitive Behavior Therapy (CBT) approach is effective in reducing hedonistic behavior in vocational high school students. It is recommended that school counselors implement CBT-based group interventions as part of student guidance programs to promote self-control, delayed gratification, and responsible lifestyle choices.